Hubungan Pengetahuan Dengan Sikap Ibu Tentang Pentingnya Peranan Gigi Sulung : Kajian Pada Ibu Di Ra Al-Irsyadiyah, Kota Tangerang (Laporan Penelitian) - Anneke Ramadhanty Putri Wardani; Tri Putriany Agustin; Jeddy Jeddy (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Primary teeth are the teeth found in the oral cavity of a child from the age of 6 months until they are replaced by permanent teeth. During their existence in the oral cavity, primary teeth play a role in a child’s development which can be seen from their functions, including as a masticatory organ, aesthetics, phonetics, and as a natural space maintainer for permanent teeth. Damage to primary teeth or premature loss of primary teeth can interfere with their function and may have an impact on the development of permanent teeth. A mother’s knowledge regarding primary teeth and their important role can form a good attitude on the mother’s part; thus, it may have an impact on how mothers care for and maintain these teeth in a healthy state to carry out their functions. Objective: To determine the correlation between mother’s knowledge and attitude regarding the importance of the role of primary teeth in the child’s oral cavity among mothers at RA Al-Irsyadiyah, Tangerang City. Method: This study is an analytic observational study with a cross sectional design by involving 51 mothers of students as respondents in RA Al-Irsyadiyah school, Tangerang City. The data were obtained by using online questionnaires. The questionnaires were distributed through the school. Results: The analysis result using the Spearman correlation test showed that p = 0.000 (p <0.05) with a positive correlation coefficient of 0.485. Conclusion: There is a significant correlation between mother’s knowledge and attitude regarding the importance of the role of primary teeth in the child’s oral cavity among mothers at RA Al-Irsyadiyah, Tangerang City.